Efeitos do exercício físico regular sobre o controle secretor de insulina em ilhotas pancreáticas isoladas de ratos obesos - Valcanaia, Ana Claudia (2018)
The breakdown of energy balance results in an accumulation of adipose tissue, associated with the development of Insulin Resistance (IR) and hyperinsulinemia. Insulin secretion (IS) is highly regulated by nutrients, especially glucose, and autonomic neural signals. This process engages oxidative metabolism and alteration of the membrane potential, resulting in calcium influx and exoctation of insulin granules in beta pancreatic cells (β). The action of glucose on β-cells initiates triggering and amplifying pathways. Together, the IS is also modulated by the Acetylcholine (ACH), Parasympathetic Nervous System (SNP) neurotransmitter. An autonomic nervous system (SNA) maladjustment characterized by parasympathetic hyperactivity with altered sensitivity to glucose and ACH, contribute to the hyperinsulinemia present in obesity. In contrast, physical exercise reduces adipose tissue, improves IR and reduces IS. However, the direct effects on pancreatic islets and glucose responsiveness are unknown. Thus, there’s the problem question: Is lifelong physical exercise capable of reducing hyperinsulinemia by modifying the glucose response and correcting the cholinergic insulinotropic effect in islets of obese rodents? Therefore, the objective of the present study was to characterize the effects of exercise on insulin secretory control in obese rats. Therefore, obesity was induced by hypothalamic lesion by monosodium glutamate (MSG, 4 g/kg) administered in the neonatal phase. Control rats (CON) received equimolar saline. After the 30th day, the animals were weaned and randomly distributed in the exercised (EXE) and sedentary (SED) groups. The exercise consisted of swimming, held three times a week, for 30 minutes throughout life. At 92 days, the rats were euthanized and anthropometric and biochemical data were collected. To evaluate glucose-induced SI, pancreatic islets were isolated and incubated in the presence of glucose (16.7 mM) and pharmacological agents that modify the effects of oxidative-glycolytic metabolism, such as diazoxide (DZ, 250 μM) or calcium channel inhibitors (Verapamil, 10 μM and tapsigargine, 20 μM). Additionally, pancreatic islets were also isolated and incubated at increasing concentrations of glucose (5.6 - 24.0 mM) or ACH (0.01 - 3000 μM) for the preparation of dose-response curves and obtaining the sensitivity to agents (EC50). The expression of the muscarinic receptor subtype 3 (MR3) major ACH was also evaluated, in addition to kinases involved in the pathway. Swimming was effective in reducing glycemia, insulinemia and triglycerides in MSG-EXE rats, compared to MSG-SED. In addition, the two groups of exercised rats had an improvement in glucose sensitivity. This event was accompanied by reduction of the glucose amplification pathway, without alteration in the expression of the proteins involved in the secretion pathway. Although pancreatic islets of MSG rats are more sensitive to blocking intracellular calcium stores, calcium responses were not modified by exercise in both groups. It is possible to conclude that the physical exercise was efficient in the reduction of the IS induced by the glucose and the cholinergic responsiveness, possibly by a decrease of the amplifying route of the secretion.